1988
DOI: 10.1111/j.1432-1033.1988.tb14019.x
|View full text |Cite
|
Sign up to set email alerts
|

The ω‐hydroxylation of arachidonic acid by human polymorphonuclear leukocytes

Abstract: Incubations of [1-'4C]arachidonic acid with unstimulated human polymorphonuclear leukocytes resulted in the formation of four new metabolites in a previously described reverse-phase HPLC system. Three of these metabolites were largely suppressed in a CO/02 (80/20, by vol.) atmosphere indicating a cytochrome-P450-dependent monooxygenase reaction. In agreement with this assumption is their NADPH/02-dependent formation in the microsomal fraction. One metabolite was identified by gas chiomatography/mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 27 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…The receptors thereby couple to intracellular signals that promote function. However, the PMN soon counteract these signals by: a) degrading phospholipid products (tl12 5 1 min), pumping Ca2' out of cytosol (t, 5 1 min), and terminating PKC mobilization (t1,2 5 0.25 min) (see previous references); b) metabolizing LTB, to less potent C-20 oxygenated derivatives (tl,2 -10 min) (Kreisle and Parker, 1983;Shak and Goldstein, 1985;O'Flaherty et al, 1986b,c;Soberman et al, 1987;Hatzelmann and Ullrich, 1988); c) decreasing LTB, receptor availability (observed at 10 min) (Goldman and Goetzl, 1984); and d) becoming insensitive to ambient LTB, (t 2 2.5 min) (O'Flaherty et al, 1981;Goldman and Goetzl, 1984;O'Flaherty, 1985). Like many other agonists, then, LTB, causes a burst of cellular excitation followed by a period of quiesence and desensitization.…”
mentioning
confidence: 99%
“…The receptors thereby couple to intracellular signals that promote function. However, the PMN soon counteract these signals by: a) degrading phospholipid products (tl12 5 1 min), pumping Ca2' out of cytosol (t, 5 1 min), and terminating PKC mobilization (t1,2 5 0.25 min) (see previous references); b) metabolizing LTB, to less potent C-20 oxygenated derivatives (tl,2 -10 min) (Kreisle and Parker, 1983;Shak and Goldstein, 1985;O'Flaherty et al, 1986b,c;Soberman et al, 1987;Hatzelmann and Ullrich, 1988); c) decreasing LTB, receptor availability (observed at 10 min) (Goldman and Goetzl, 1984); and d) becoming insensitive to ambient LTB, (t 2 2.5 min) (O'Flaherty et al, 1981;Goldman and Goetzl, 1984;O'Flaherty, 1985). Like many other agonists, then, LTB, causes a burst of cellular excitation followed by a period of quiesence and desensitization.…”
mentioning
confidence: 99%
“…Synthetic 20-HETE and 19(S)-HETE were a gift from Dr J. R. Falck (University of Texas, Southwest Medical Center, Dallas, Texas). 5,6,8,9,11,12,14,1 5-(3H)LTB, (220 Ci mmol-') was obtained from Dupont-New England Nuclear, and ("O)H,O was obtained from Isotec Inc. (Miamisburg, Ohio). Formylmethionylleucylphenylalanine (FMLP) was obtained from Sigma Chemical Co. (St Louis, Missouri); l-O-hexadecyl-2acetylglycerophosphocholine (PAF) was obtained from Bachem (Bubendorf, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…Hepatocytes as well as unstimulated neutrophils have also been found to transform exogenous free arachiconic acid into this metabolite (Hatzelmann & Ullrich, 1988;. Recently, 20-HETE biosynthesis was found to be elevated in the kidneys of young spontaneous hypertensive rats (Sacerdoti et al, 1988).…”
Section: Camentioning
confidence: 99%
“…Hepatocytes , renal cortical, and medulla preparations (Morrison & Pascoe, 1981;Oliw et al, 1981;Schwartzman et al, 1986;Takahashi et al, 1990) contain an active cytochrome P-450 which readily catalyzes the formation of 20-hydroxyeicosatetraenoic acid (20-HETE) as well as . In addition, 20-HETE is a major metabolite of arachidonic acid formed within the resting polymorphonuclear leukocyte (PMN) following the addition of exogenous arachidonic acid (Hatzelmann & Ullrich, 1988).…”
Section: Introductionmentioning
confidence: 99%